Contagionism and Contagious Diseases : Medicine and Literature 1880-1933. - Rütten, Thomas (Spectrum Literaturwissenschaft / spectrum Literature., 2014)
Understanding how 'contagion' and 'infection' have become powerful metaphors requires a historical reconstruction of this semantic field in the late 19th and early 20th century, when these concepts acquired a scientific meaning. The volume offers an interdisciplinary approach to the cultural history of contagionism between medical bacteriology, the social sciences and literary adaptations. The symbolic implications of 'contagion' and high-profile contagious diseases are addressed, which mark the boundaries between sick and healthy, familiar and alien, morally pure and impure.